2021
DOI: 10.1002/hbm.25418
|View full text |Cite
|
Sign up to set email alerts
|

Graph theoretical analysis of evoked potentials shows network influence of epileptogenic mesial temporal region

Abstract: It is now widely accepted that seizures arise from the coordinated activity of epileptic networks, and as a result, traditional methods of analyzing seizures have been augmented by techniques like single‐pulse electrical stimulation (SPES) that estimate effective connectivity in brain networks. We used SPES and graph analytics in 18 patients undergoing intracranial EEG monitoring to investigate effective connectivity between recording sites within and outside mesial temporal structures. We compared evoked pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This connectivity asymmetry across hemispheres is in line with findings of other studies, which have demonstrated a decreased functional connectivity within the epileptogenic hippocampal networks with a concurrent increased connectivity in contralateral hippocampal pathways, possibly reflecting compensatory mechanisms with strengthening of alternative pathways in these patients. 110,[114][115][116] To that end, the connectivity patterns and natural sink-like behavior of the hippocampus need to be taken into consideration as results of the source-sink analysis are reviewed and interpreted. Although the tool performs well with the hippocampal electrodes included in the datasets, as reflected by our results, there might be cases where these electrodes could simply be removed (e.g., clinical experts are certain that the hippocampus is not involved in seizure onsetand hippocampus was only targeted to rule out temporal epilepsy or determine spread and thus would ignore these electrodes in their standard of care analyses).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This connectivity asymmetry across hemispheres is in line with findings of other studies, which have demonstrated a decreased functional connectivity within the epileptogenic hippocampal networks with a concurrent increased connectivity in contralateral hippocampal pathways, possibly reflecting compensatory mechanisms with strengthening of alternative pathways in these patients. 110,[114][115][116] To that end, the connectivity patterns and natural sink-like behavior of the hippocampus need to be taken into consideration as results of the source-sink analysis are reviewed and interpreted. Although the tool performs well with the hippocampal electrodes included in the datasets, as reflected by our results, there might be cases where these electrodes could simply be removed (e.g., clinical experts are certain that the hippocampus is not involved in seizure onsetand hippocampus was only targeted to rule out temporal epilepsy or determine spread and thus would ignore these electrodes in their standard of care analyses).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with electrodes targeting the hippocampal region, the hippocampal contacts were frequently identified as top sinks in the iEEG network. The hippocampus is a highly connected structure, with many bidirectional connections within and to surrounding regions 110 both intra- and inter-hemispherically. 111 Further, studies of mesial temporal lobe epilepsy (MTLE) have demonstrated the existence of strong connections within the hippocampal network bilaterally in both epileptogenic as well as non-epileptogenic hippocampi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations